Effect of Main Factors on Fracture Mode of Mortar, A Graphical Study - Sahar Mahdinia; Hamid Eskandari-Naddaf; Rasoul Shadnia (Salehan Institute of Higher Education, 2017)
One of the most effective ways to identify the concrete properties is to understand further about the cement mortar, which is a mixture of cement paste and fine aggregate. In order to identify the behavior of cement mortar, all required materials including cement, fine aggregate, water as well as the different ratios of each material should beinvestigated. The main objective of this research is to study the effectiveness of main parameters of mortar on the fracture mode and related factors. Specifically 26 mixing designs of flexural mortar with three cement strength classes (32.5, 42.5 and 52.5 MPa), three water to cement (W/C) ratios (0.25, 0.3 and 0.35) and three sand to cement (S/C) ratios (2.5, 2.75 and 3) were first prepared. The prepared samples were then tested using a stress-strain apparatus. Some pictures were finally taken from the fracture surfaces to investigate the mode and angle of fractures. The results indicated that any change in the main parameters of mortar changes the fracture mode and the fracture angle.